Efficient filtering structure for spline interpolation and decimation. Issue 1 (1st January 2016) - Lamb, D.; Chamon, L.F.O.; Nascimento, V.H.
Abstract : An efficient structure for spline‐based fractional delay filtering for interpolation/decimation is introduced. Inspired by the Newton structures for Lagrange interpolation, it requires less than half the number of operations of a typical Farrow implementation. Moreover, it displays better frequency response characteristics than Lagrange‐based filters. To obtain this structure, a matrix form of the Farrow transfer function is proposed and used to derive state‐space transformations between the Lagrange‐Farrow structure and its Newton counterpart. These transformations are then applied to the spline polynomial, giving rise to the efficient Newton‐like spline filtering method.